Pengaturan Tindak Pidana Penghinaan Presiden dalam KUHP Nasional Ditinjau dari Prinsip Kebebasan Berpendapat di Indonesia - Stephanus Dandy Hayon; Frans Simangunsong (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Through Articles 218 and 219, Law Number 1 of 2023 on the Criminal Code brings back the criminal offense of insulting the President and Vice President, notwithstanding that a comparable provision had earlier been struck down by the Constitutional Court in Decision Number 013-022/PUU-IV/2006. This paper assesses the extent to which the offense of insulting the President under the National Criminal Code aligns with the freedom of expression guaranteed by the 1945 Constitution and situates the provision within a comparative examination of similar rules in other countries. The study relies on a normative legal method combining statutory, conceptual, and comparative approaches. Findings suggest that the provision does not fundamentally conflict with freedom of expression, given that the National Criminal Code converts the offense into a complaint-based offense (delik aduan) and carves out exceptions for criticism made in the public interest or self-defense. Even so, the phrase “attacking the honor or dignity” continues to leave room for expansive interpretation, calling for careful and measured enforcement so that legitimate criticism within a democracy is not stifled.